A Effect of Influencer Marketing and Online Customer Review On Online Purchasing Decisions (Case study on Generation Z as Shopee Users in Karawang Regency) - Nuruh Wahyuni, Nurul; Ina Ratnasari, Ina (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
The purpose of this study is to ascertain whether online customer reviews and influencer marketing have an impact on the online buying decisions of Generation Z Shopee customers in Karawang Regency. The research uses Nonprobability Sampling and purposive sampling methods, focusing on all population members with specific relevant criteria. A sample of 100 respondents was selected, and data processing was conducted using SPSS version 25. Multiple Linear Regression Analysis is the method used for data analysis in this article. The results of the questionnaires used for data collection were the main source of information used to evaluate the influence of online customer reviews and influencer marketing on the online buying decisions of Generation Z Shopee users in Karawang Regency. The study’s conclusions show that Generation Z Shopee customers in Karawang Regency are heavily influenced by influencer marketing as well as online customer reviews when making selections about what to buy online. These findings underscore the significance of social media personalities in the decision-making process and suggest that influencer marketing is a key factor in influencing the purchasing behavior of young customers. Similarly, online customer reviews provide valuable peer feedback that Generation Z heavily relies on when making online purchases. The research underscores the significance of these factors in the digital marketing landscape, offering insights for businesses aiming to target and engage Generation Z effectively. Through comprehension of the effects of influencer marketing and online customer evaluations, marketers may create more focused approaches to appeal to this socially conscious and tech-savvy audience.